2016
DOI: 10.3109/10826084.2015.1092987
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cigarette Smoking Among Rural-to-Urban Migrants in China: A Systematic Review and Meta-Analysis

Abstract: Cigarette smoking is still prevalent among rural-to-urban migrants, which may be influenced by gender and occupations. Policies should be designed and conducted to control smoking prevalence among these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
8
18
0
Order By: Relevance
“…The migrants engaged in construction sector have more likelihood to smoke than the other sectors. It is consistent with the general conclusion that smoking behavior is more prevalence among the construction rural workers due to its high stress job [8].The migrants engaging in over-time job are at a higher level of risk for cigarette smoking, which implies that over-time work may induce a high level of psychosocial stress and high rates of mental problems for migrant workers, which in turn increase the susceptibility to cigarette smoking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The migrants engaged in construction sector have more likelihood to smoke than the other sectors. It is consistent with the general conclusion that smoking behavior is more prevalence among the construction rural workers due to its high stress job [8].The migrants engaging in over-time job are at a higher level of risk for cigarette smoking, which implies that over-time work may induce a high level of psychosocial stress and high rates of mental problems for migrant workers, which in turn increase the susceptibility to cigarette smoking.…”
Section: Discussionsupporting
confidence: 88%
“…However, a large part of them are highly susceptible to smoking [5][6][7]. A rich array of studies has explored the determinants of rural migrants' smoking prevalence [8]. Most previous researches have consistently concluded that life and work stress are main determinants for the smoking prevalence of rural migrants [9,10], where the life and work stress include but not are limited to low-quality employment, poor living conditions, unequal public service ,maladaptation to urban life and so on [9,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco is a habit originating in cities [45,46] and so elder participants in the current sample who live in villages at high elevation tend to be non-smokers. Chromosomal changes that can cause NPB and NB become more frequent with age [4].…”
Section: Discussionmentioning
confidence: 94%
“…The smoking rate among women was also slightly lower than that in the general population (46.71% for Chinese men and 5.34% for Chinese women) [7]. Recently, the morbidity and mortality of CVD and cerebrovascular diseases have decreased in America [22] as a result of good control of CVD risk factors, of which decreased smoking rate is an important one.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle factors like smoking and alcohol consumption are also well known to increase the risk of CVD and cerebrovascular disease. Chinese women smoke less than women in the West [7], and they also have lower prevalence of alcohol dependence [8]. However, metabolic control in Chinese women with T2DM has not been clearly elucidated, and it remains largely unknown whether the risk of CVD and cerebrovascular disease in women with T2DM is higher than that in men with T2DM.…”
Section: Introductionmentioning
confidence: 99%